Nurses in action: An introduction to action research in nursing - E. C. McKibbin; P. J. Castle (Curationis, 1996)
Action Research is one of the new generation of qualitative research methods in the social sciences which has special significance for nurses in South Africa. The collaborative, participative and reflective qualities of Action Research appeal to practitioners, and lend themselves to joint problem solving activities in local contexts. This paper sets out a rationale for Action Research, then describes its features, strengths, and limitations. Ways of overcoming the latter are suggested. The paper concludes that Action Research has potential application in the field of nursing, not only for the purposes of practical problem solving, but also for improving the personal and professional practice of nurses, and for emancipating nurses from their subordinate position in the hierarchy of health science.